2020
DOI: 10.3390/su12062256
|View full text |Cite
|
Sign up to set email alerts
|

Grass–Legume Forage Systems Effect on Phosphorus Removal from a Grassland Historically Irrigated with Reclaimed Wastewater

Abstract: The utilization of reclaimed wastewater is a suitable and sustainable approach to agriculture production in water-scarce regions. However, even though the wastewater is treated to reduce nutrient concentration such as phosphorus, the 10,600 to 14,006 m3 of water applied ha−1 year−1 on grass and alfalfa hay crops in Nevada can lead to soil phosphorus buildup over an extended period. This study evaluated the effectiveness of forage systems (FS) of monoculture grass, monoculture legume, and their mixtures on herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…However, its P was similar to that of Mulato II. The discrepancies of macro-elements between shrubs and grasses was expected because shrub legumes have higher uptake of these minerals (Pant et al, 2004;Mclennon et al, 2020). The high P in Mulato II in comparison to shrub legume has been reported in semi-arid and acidic soil prone areas of Rwanda (Mutimura and Everson, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…However, its P was similar to that of Mulato II. The discrepancies of macro-elements between shrubs and grasses was expected because shrub legumes have higher uptake of these minerals (Pant et al, 2004;Mclennon et al, 2020). The high P in Mulato II in comparison to shrub legume has been reported in semi-arid and acidic soil prone areas of Rwanda (Mutimura and Everson, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…These practices create vegetative buffer strips along water bodies [ 33 , 34 ]. The implementation of these buffer strips also includes grass–legume forage systems [ 35 ] combined with the best nutrient management efforts such as the land application of P-sorbing materials; treating manure with aluminum sulfate; increasing plant P use efficiencies; and increasing the N:P ratio of manure [ 36 , 37 ]. However, these best management practices can be more effective on sediment-bound P in the runoff, but less effective in reducing dissolved P loss from sandy soils on the Delmarva Peninsula [ 38 , 39 ].…”
Section: Management Practices That Reduce Agricultural Losses Of Lega...mentioning
confidence: 99%
“…It also increased dry matter production, crude protein yield and in vitro dry matter digestibility and decreased the fiber fractions. Mclennon et al (2020) reported that grass-legume mixture at 75:25 produced greater herbage than 25:75 grass-legume mixture and legume monoculture. Forage species mixtures (grass + legume) have showed increased total forage biomass production including nutrient content when compared to growing single species (Belanger et al 2014;Cardinale, et al 2007;Foster et al 2019).…”
Section: Introductionmentioning
confidence: 99%